Pengembangan Pengetahuan Pada Ibu Hamil Tentang Diabetes Melitus Gestasional (DMG) Melalui Konseling Di Wilayah Kerja Puskesmas Tanralili - Nur Ismi Wahyuni; Sukmawati Sukmawati; Ekayanti Ekayanti (Jurnal Keperawatan Muhammadiyah, 2021)
Pregnant women with Gestational Diabetes Mellitus (GDM) almost never have symptom even though the incidence of GDM can be life threatening and very dangerous as it can cause several complications during pregnancy, childbirth, and postpartum. It is also one of the risk factors of maternal and infant mortality. The GDM can be prevented with early diagnosis or screening and intensive counseling from medical professionals. Therefore, it is expected that pregnant women have sufficient knowledge and awareness regarding GDM to prevent the GDM. Aim: The study aimed to understand the differences of knowledge among pregnant women after counseling and without counseling about GDM, and to conduct screening or early detection of GDM on pregnant women in Tanralili Public Health Center.Method: This is a quantitative study with quasi experimental research design. The research design used was pre-posttest with control group. The population was all pregnant women registered at the Tanralili Public Health Center. The sample size was 20 pregnant women consisting of 10 pregnant women who were given the intervention and 10 pregnant women as controls. The study used accidental sampling technique.Result: The study showed form statistical analysis with Wilcoxon test that p value for the knowledge in intervention group was 0.008 or <0.5, while p value for the control group was0.285 or > 0.05. This statistical result clearly showed that was a difference between the intervention group and the control group. Additionally, Mann-Whitney test obtained p value = 0.001 < = 0.05 meaning that the counseling had positive impact on the development of knowledge regarding GDM among pregnant womenDiscussion: The differences of knowledge among pregnant women after effective individual counseling in accordance with the purpose of counseling is to provide assistance to individuals to develop knowledge so that attitudes and behavioral changes can occur among pregnant women.Conclusions: There was a difference in knowledge of pregnant women about Gestational Diabetes Mellitus (DMG) between the experimental groups and control group. Additionally, there was influence of counseling on the development of knowledge of pregnant women about Gestational Diabetes Mellitus (GDM).Key Words: Counseling, Knowledge, Gestational Diabetes Mellitus